Factors influencing accounting undergraduates' career choice in chartered accountancy - Ramlan, Mohd. Raime; Ishak, Rokiah; Md Yusof, Mohd 'Atef (Universiti Utara Malaysia, 2003)
This study is carried out to determine factors that influence accounting undergraduates in career choice as chartered accountancy. Replicating model developed by Felton et al. (1994) and Kamran et al. (1997), this study also aims to investigate whether there is a difference of gender and students' achievement towards their career choice to become chartered accountant. A total of 668 final year accounting students replied as respondents using a questionnaire. The results from logistic and MDA regression analysis indicate that UUM accounting undergraduates place higher weights on the image of the profession, benefits and costs and intrinsic value when deciding to join a career in chartered accountancy. The results also suggest male and female students are different when choosing a career in chartered accountancy. However, we found students' academic excellence is insignificant in influencing student's career choice in chartered accountancy. The study recommends for accounting firms and accounting professions to make chartered accountancy become more attractive in term of non-monetary rewards, offer more benefits and provide motivational aspects at educational level in order to improve undergraduates' perception on chartered accountancy. More ever, recruiters from big accounting firms and commercial sectors should also play more active role to attract prospective accounting undergraduates through career talk and effective recruitment schemes.